Prospek Penjualan Ikan Hias di Pasar Ikan Hias Tegallega Kota Bandung Jawa Barat - Gumilar, Iwang; Ghifari, Naufal Hasvi; Zahidah, Zahidah; Maulina, Ine (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to analyze the sales prospects of ornamental fish at the Tegallega Ornamental Fish Market, Bandung City. The research method used in this research is the survey method. The type of data used is primary data obtained by interviews using questionnaires and field observations, and secondary data obtained by collecting institutional data and the results of scientific publications. The number of samples in this study was 40 people spread across Tegallega, Bandung City. The sampling technique used was purposive sampling technique. The data analysis method used is a quantitative descriptive analysis method. The analytical parameters used to analyze ornamental fish sales prospects include financial parameters such as profit, B/C, Break Even Point, and Payback Periods. The results of the research show that the sale of ornamental fish at the Tegallega Ornamental Fish Market, Bandung City has good prospects and is feasible. This is indicated by meeting the eligibility criteria for all financial parameters. The results of the analysis of sales prospects for ornamental fish using data for 1 year of sales show that sales at the Tegallega Ornamental Fish Market are classified as good, as profits are positive with a value of Rp. 129,720,000; B/C value is more than 1 with a value of 1.4; Break Even Point value of IDR 110,275,542 or sales volume of 3,958 head/year; and the Payback Period value is less than 1 year, namely 0.55 years.